CAR-T cell therapy: Efficacy in management of cancers, adverse effects, dose-limiting toxicities and long-term follow up - Mohamed Elmarasi (14614276) (2024)
Chimeric Antigen Receptor T-cell (CAR-T) therapy has emerged as a groundbreaking and highly promising approach for the management of cancer. This paper reviews the efficacy of CAR-T therapy in the treatment of various hematological malignancies, also, with a mention of its effect on solid tumors, for which they have not received FDA approval yet. Different common and uncommon side effects are also discussed in this paper, with attention to the effect of each drug separately. By reviewing the recommendations of the FDA for CAR-T therapy research, we have extensively discussed dose-limiting toxicities. This further highlights the need for precise dosing strategies, striking a balance between therapeutic benefits and potential risks. Additionally, we reviewed the long-term follow-up of patients receiving CAR-T therapy to gain valuable insights into response durability and late-onset effects. Other Information Published in: International Immunopharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.intimp.2024.112312